PROPERTIES OF IMMOBILIZED LIPASE FROM Rhizopus delemar ON POLYPROPYLENE MEMBRANE = SIFAT-SIFAT ENZIM LIPASE AMOBIL DARI Rhizopus delemar DALAM MEMBRAN POLIPROPILEN - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT Properties of Rhizopus delemar lipase immobilized on hydrophobic polypropylene membrane were studied by physical adsorption using various concentration of enzyme loading. The result shows that free fatty acid liberation was affected by the enzyme loading, which increased with the increasing enzyme loading. The maximum enzyme adsorption was achieved at 1.2 mg/cm2 membrane. The initial velocity of hydrolysis reaction seems not to be affected by the amount of enzyme bound. The immobilization efficiency was very high reaching more than 60 % at enzyme loading of 0.3 mg/cm2, although a suppression of efficiency was detected at higher loading. The immobilized lipase could hydrolyze 97 % olive oil after 72 h using 1 mg/cm2 of initial enzyme loading. The kinetic parameter indicated that the affinity of the enzyme to substrate was very low (Km = 183 mg/mI). The immobilized enzyme was very stable during storage at 4 Â°C with proximate half life 65 days. In addition, it maintains ability for subsequent reuses. The membrane can be regenerated by washing for fresh enzyme immobilization.